Characteristics of modern system of training athletes in rowing - Orlova V. V., Khalaleeva O. E. (Humanitarian, 2016)
this article presents the main stages of development and professional growth of athletes specialised in rowing. The authors considered the characteristics of modern system of qualified athletes training, challenges that must be addressed at every stage and methodological aspects of their solutions at each stage of a training the qualified athlete. The necessity of training the athlete not only from the technical point of view, but also according to safety rules is grounded. Significant attention in the assessment of the quality and efficiency of the methodology for training professional athletes in rowing is paid to performance requirements permitting to assess the athlete’s degree of involvement in training process and his real level at the moment.
Keywords: методология; methodology; аспекты; современная система подготовки; квалифицированные спортсмены; академическая гребля; aspects; modern system of training; qualified athletes; rowing